Identification of pathogenic variants for the development of ultra-long axial length in myopic children - YanYing Zhu; Xueyan Li; YueXin Chen; HaiYan Xie; Yukun Liu; XiaoChen Xu; Jing Wang (PLoS ONE, 2025)
Purpose Axial elongation is a key factor in myopia progression, yet its genetic basis remains incompletely understood. This study aims to identify pathogenic genetic variants associated with excessively elongated axial length in children. Methods This study included 56 children with axial lengths exceeding the normal range for their age group, and whole-exome sequencing (WES) was performed on their oral mucosal samples. Clinical evaluations included axial length measurement, refraction testing, and fundus photography to assess the degree of myopia and retinal changes. Co-segregation analysis was conducted in selected families (F#1, F#2, F#5) to validate the familial inheritance patterns of the variants. Results Fifteen children carried variants in genes including BBS2, OPN1LW, P4HA2, FBN1, LOXL3, FZD4, USH2A, COL2A1, and BFSP2, with five novel variants identified: BBS2 (c.700C > T), P4HA2 (c.1382C > G), FBN1 (c.7130T > C), LOXL3 (c.1580delC), and FZD4 (c.1315G > A). Notably, a rare compound heterozygous BBS2 variant (c.700C > T/c.534 + 1G > T) was found in a non-syndromic child, and the P4HA2 (c.419A > G) variant in family F#5 exhibited a phenotype distinct from previous studies. Conclusions This study identified five novel variants sites and discovered two cases with phenotypes distinct from previous studies, thereby expanding the genetic variant spectrum associated with myopia and providing new targets for genetic screening and intervention.